ON THE EXCHANGE RATE PASS-THROUGH INTO INFLATION IN ROMANIA – A DISCUSSION - Ana-Maria Barsan; Alexandra Horobet (European Scientific Journal, ESJ, 2014)
The significance of the exchange rate for Romania’ macroeconomic policies raised the level of interest related to the study of relationships between the exchange rate and the other macroeconomic variables, and particularly inflation, given the realities of a small open economy. Given the country’s membership to the European Union and the declared intention to adopt the Euro, Romania has to fulfil the Maastricht criteria for nominal convergence. At present, these criteria are met only in terms of the fiscal deficit and public debt, while the other criteria remain to be complied with, including here the inflation rate. Our paper’s objective is to discuss the influence of the exchange rates on one of the most followed macroeconomic variables – the inflation rate –, using the concept of exchange rate passthrough, and to provide an assessment of Romania’s macroeconomic conditions with respect to exchange rates and inflation, with an eye over the eventual fulfilment of Maastricht criteria needed for Euro adoption. We conclude that although Romania has achieved an all-time low annual inflation rate of 1.55% at end of 2013 Q4, and the forecasts until 2015 are optimistic regarding inflation targeting, a higher volatility in the exchange rate, as observed towards the end of 2013, which can encourage a higher degree of exchange rate pass-through into inflation, coupled with expected populist measures in an electoral year (2014) might endanger the central bank’s objective to maintain inflation within the announced target of 2.5%.